Penanaman Karakter Santri Taman Pendidikan Al-Qur’an Al-Umm Kroya - Nurul Azizah; Asep Amaludin (Idea Pengabdian Masyarakat, 2022)
This article describes the character planting of the students of the Al-Qur'an Education Park or TPA. Al-Qur'an Education Park is an educational institution where children can learn and play under the guidance of a teacher or cleric. Character formation is a form of government efforts to form a generation that has character. In realizing this, support from all parties is needed, including TPA. Character education is an effort to create a generation that has ethics, morals and morality. This type of research is a qualitative descriptive study conducted at TPA al-umm. Data collection techniques using interviews, observation and documentation. The results of the analysis of this study are that the teacher carries out several stages in inculcating the character of the santri alumm, the stages of this activity are the first religious moderation lecture activities, the second provides a good example that can be followed by the santi. The third is providing religious teaching that will add insight to the students in the TPA. This activity aims to shape children's character better than before. The method of implementing community service activities is to participate in the field directly. The result of this community service activity is the creation of a generation that has good morals and a broad understanding of religion.